Return to Sport and Work after Randomization for Knee Distraction versus High Tibial Osteotomy: Is There a Difference? - Hoorntje, Alexander; Kuijer, P. Paul F. M.; Koenraadt, Koen L. M.; Waterval-Witjes, Suzanne; Kerkhoffs, Gino M. M. J.; Mastbergen, Simon C.; Marijnissen, Anne C. A.; Jansen, Mylène P.; van Geenen, Rutger C. I. (The Journal of Knee Surgery, 2020)
Knee joint distraction (KJD) is a novel technique for relatively young knee osteoarthritis (OA) patients. With KJD, an external distraction device creates temporary total absence of contact between cartilage surfaces, which results in pain relief and possibly limits the progression of knee OA. Recently, KJD showed similar clinical outcomes compared with high tibial osteotomy (HTO). Yet, no comparative data exist regarding return to sport (RTS) and return to work (RTW) after KJD. Therefore, our aim was to compare RTS and RTW between KJD and HTO. We performed a cross-sectional follow-up study in patients <65 years who previously participated in a randomized controlled trial comparing KJD and HTO. Out of 62 eligible patients, 55 patients responded and 51 completed the questionnaire (16 KJDs and 35 HTOs) at 5-year follow-up. The primary outcome measures were the percentages of RTS and RTW. Secondary outcome measures included time to RTS/RTW, and pre- and postoperative Tegner's (higher is more active), and Work Osteoarthritis or Joint-Replacement Questionnaire (WORQ) scores (higher is better work ability). Patients' baseline characteristics did not differ. Total 1 year after KJD, 79% returned to sport versus 80% after HTO (not significant [n.s.]). RTS <6 months was 73 and 75%, respectively (n.s.). RTW 1 year after KJD was 94 versus 97% after HTO (n.s.), and 91 versus 87% <6 months (n.s.). The median Tegner's score decreased from 5.0 to 3.5 after KJD, and from 5.0 to 3.0 after HTO (n.s.). The mean WORQ score improvement was higher after HTO (16 ± 16) than after KJD (6 ± 13; p = 0.04). Thus, no differences were found for sport and work participation between KJD and HTO in our small, though first ever, cohort. Overall, these findings may support further investigation into KJD as a possible joint-preserving option for challenging “young” knee OA patients. The level of evidence is III.
Keywords: high tibial osteotomy; knee joint distraction; return to sport; return to work; physical activity